Predictive biomarkers and initial analysis of maternal immune alterations in postpartum preeclampsia reveal an immune-driven pathology - Couture, Camille; Brien, Marie-Eve; Rechtzigel, Jade; Ling, SuYun; Ledezma-Soto, Cecilia; Duran Bishop, Gilberto; Boufaied, Ines; Dal Soglio, Dorothée; Rey, Evelyne; McGraw, Serge; Graham, Charles H.; Girard, Sylvie (Frontiers in Immunology, 2024)
Postpartum preeclampsia (PPPE) is an under-diagnosed condition, developing within 48 hours to 6 weeks following an uncomplicated pregnancy. The etiology of PPPE is still unknown, leaving patients vulnerable and making the identification and treatment of patients requiring postpartum care an unmet need. We aimed to understand the immune contribution to PPPE at the time of diagnosis, as well as uncover the predictive potential of perinatal biomarkers for the early postnatal identification of high-risk patients. Placentas were collected at delivery from uncomplicated pregnancies (CTL) and PPPE patients for immunohistochemistry analysis. In this initial study, blood samples in PPPE patients were collected at the time of PPPE diagnosis (48h-25 days postpartum; mean 7.4 days) and compared to CTL blood samples taken 24h after delivery. Single-cell transcriptomics, flow cytometry, intracellular cytokine staining, and the circulating levels of inflammatory mediators were evaluated in the blood. Placental CD163+ cells and 1 st trimester blood pressures can be valuable non-invasive and predictive biomarkers of PPPE with strong clinical application prospects. Furthermore, changes in immune cell populations, as well as cytokine production by CD14+, CD4+, and CD8+ cells, suggested a dampened response with an exhausted phenotype including decreased IL1b, IL12, and IFNg as well as elevated IL10. Understanding maternal immune changes at the time of diagnosis and prenatally within the placenta in our sizable cohort will serve as groundwork for pre-clinical and clinical research, as well as guiding clinical practice for example in the development of immune-targeted therapies, and early postnatal identification of patients who would benefit from more thorough follow-ups and risk education in the weeks following an uncomplicated pregnancy.